2009
DOI: 10.1074/jbc.m806855200
|View full text |Cite
|
Sign up to set email alerts
|

Agrin Regulation of α3 Sodium-Potassium ATPase Activity Modulates Cardiac Myocyte Contraction

Abstract: Drugs that inhibit Na,K-ATPases, such as digoxin and ouabain, alter cardiac myocyte contractility. We recently demonstrated that agrin, a protein first identified at the vertebrate neuromuscular junction, binds to and regulates the activity of ␣3 subunit-containing isoforms of the Na,K-ATPase in the mammalian brain. Both agrin and the ␣3 Na,K-ATPase are expressed in heart, but their potential for interaction and effect on cardiac myocyte function was unknown. Here we show that agrin binds to the ␣3 subunit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Moreover, we know that only the animal hemisphere of the stage‐VI oocyte is responsive to progesterone. Similarly, Hilgenberg et al (2006, 2009) have shown that the α3‐subunit of Na + ,K + ‐ATPase acts as a receptor for Agrin (both in neuronal and cardiac tissues), which down‐regulates Na + ,K + ‐ATPase activity and modulates membrane potential and action potential frequencies of cortical neurons and cardiomyocytes contraction.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, we know that only the animal hemisphere of the stage‐VI oocyte is responsive to progesterone. Similarly, Hilgenberg et al (2006, 2009) have shown that the α3‐subunit of Na + ,K + ‐ATPase acts as a receptor for Agrin (both in neuronal and cardiac tissues), which down‐regulates Na + ,K + ‐ATPase activity and modulates membrane potential and action potential frequencies of cortical neurons and cardiomyocytes contraction.…”
Section: Resultsmentioning
confidence: 92%
“…During early development of Xenopus, Na + ,K + ‐ATPase activity has been implicated in blastocoel formation (Slack et al, 1973), for the maintenance of neural plate potentials (Blackshaw and Warner, 1976), and in neuronal differentiation (Messenger and Warner, 2000). Na + ,K + ‐ATPase has also recently been found to have roles in cell adhesion (Shoshani et al, 2005), cell polarity (Laprise et al, 2009), phosphotidylinositol 3‐kinase (Barwe et al, 2005), and Src kinase signaling (Xie and Askari, 2002), endocytosis (Cai et al, 2008), tubulogenesis (Krupinski and Beitel, 2009), tight junction formation (Rajasekaran et al, 2005), and as receptor for progesterone (Morrill et al, 2005) and Agrin (Hilgenberg et al, 2006, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Another ion channel proteins that we identified to be putatively associated with Dg are -ATPα and Nrv1 (Nervana1), which are αand β-subunits of the Na + , K + ATPase ion pump important for maintaining cellular membrane potential in the muscles [97]. Previous studies report that the activity of α3 Na + , K + ATPase can be modulated by the ECM protein Agrin in mouse cardiac myocytes, influencing their contraction [98]. The Nterminal region of Agrin binds laminin, while the Cterminal end binds to several transmembrane ECM receptors, including Dg; however, whether Agrin-linked regulation of Na + , K + ion pump depends on Dg remains unrevealed.…”
Section: Membrane-associated Proteinsmentioning
confidence: 98%
“…44 In a study of ATP1A3 mutant mice, “restraint stress” was found to induce significant deficits in motor coordination and balance, as well as decreased thermal sensitivity and alterations in monoamine metabolism. 38 An impact on function or expression of the cardiac-specific alpha3 isomer 45 could provide an alternative explanation for autonomic dysfunction.…”
Section: Atp1a3 Pathophysiologymentioning
confidence: 99%